PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA DI KELAS XI IPS MA YPKM LUBUK JAMBI - Heni Kumala Sari; Suhermi Suhermi; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRAKThe research was done in MA YPKM Lubuk Jambi, in the second semester of academic year 2012/2013. The subjects were students of class XI IPS. There is a class of 15 students, consisting of 9 men and 6 women who have heterogeneous capabilities. The purpose of this research is to improve mathematics learning outcomes, especially in basic competencies using derivatives to determine the characteristics of a function and solve the problem, the basic competencies devised a mathematical model of the problems associated with extreme functionality and basic competency describes mathematical models of the problems associated with extreme functionality and interpretation through problem-solving strategies in tife STAD cooperative learning model.This study is a class action. There are two cycles and four stages, planning, action, observation and reflection. The results showed that an increase in student achievement. The first cycle shows that the percentage of students who receive a minimum completeness criteria of 20% to 26.7%. While in the second cycle, the percentage achievement of minimum completeness criteria increased from 26.7% to 86.7%, in other words, the implementation of the application of problem solving strategies in STAD cooperative learning model to improve learning outcomes of students in class XI maths IPS MA YPKM Lubuk Jambi , on the basis of competence using derivatives to determine the characteristics of a function and solve the problem, the basic competencies devised a mathematical model of the problems associated with extreme functionality and basic competency describes mathematical models of the problems associated with extreme functionality and interpretation. Keywords: STAD cooperative, problem-solving strategies, classroom action research